Is a distributed research program an effective model for implementing R4D? Researchers need to collaborate to address grand challenges such as climate change, poverty and sustainable food production. This study investigates how the researchers in a globally distributed research program (CCAFS) interact to move their research forward - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
This study is (in essence) an evaluation of how FP1 functions as a distributed research program. Some of the evaluation will be relevant for other CCAFS flagships too.